Use of eggshell membranes in regenerative medicine: A brief bibliometric analysis: Uso de membranas de cáscara de huevo en medicina regenerativa: Un breve análisis bibliométrico - Huamani-Huaracca, Ana (2025)
The use of eggshell membranes has been essential in aspects of practical medicine. Identifying knowledge gaps is essential to promote future research and improve the inclusivity and depth of critical areas identified in the current literature. This warrants attention to aspects that guarantee approaches to investigating the properties of this biomaterial in regenerative treatments.